Pentaquark molecular states with hidden bottom and double strangeness - Jing Song; Man-Yu Duan; Luis Roca; Eulogio Oset (European Physical Journal C: Particles and Fields)
Abstract We investigate the meson-baryon interaction in coupled channels with the quantum numbers of the pentaquarks $$P_{bss}$$ P bss and $$P_{bsss}$$ P bsss . The interaction is derived from an extension of the local hidden gauge approach to the heavy quark sector, which has demonstrated accurate results compared to experiments involving $$Ω _{b}$$ Ω b , $$Ξ _{b}$$ Ξ b states, and pentaquarks $$P_{c}$$ P c and $$P_{cs}$$ P cs . In our study, we identify several molecular states with small decay widths within the chosen set of coupled channels. The spin-parity ( $$J^P$$ J P ) of these states is as follows: $$J^P={\frac{1}{2}}^-$$ J P = 1 2 - for pseudoscalar-baryon ( $${\frac{1}{2}}^+$$ 1 2 + ) coupled channels, $$J^P={\frac{3}{2}}^-$$ J P = 3 2 - for pseudoscalar-baryon ( $${\frac{3}{2}}^+$$ 3 2 + ) coupled channels, $$J^P={\frac{1}{2}}^-$$ J P = 1 2 - and $${\frac{3}{2}}^-$$ 3 2 - for vector-baryon ( $${\frac{1}{2}}^+$$ 1 2 + ) coupled channels, and $$J^P={\frac{1}{2}}^-$$ J P = 1 2 - , $${\frac{3}{2}}^-$$ 3 2 - , $${\frac{5}{2}}^-$$ 5 2 - for vector-baryon ( $${\frac{3}{2}}^+$$ 3 2 + ) coupled channels. We search for the poles of these states and evaluate their couplings to the different channels.